Strategi Supervisi Kepala Sekolah dalam Meningkatkan Kinerja Guru Pendidikan Agama Islam - Arrochman, Ichromsyah (TAUJIH: Jurnal Pendidikan Islam, 2023)
One of the programs that can be held to improve the quality of learning is the implementation of assistance to teachers or better known as supervision. The Principal as an educational leader in the school has a duty in the field of supervision. and the purpose of this study is to determine the Principal's Supervision Strategy in improving the performance of Islamic Education teachers at SDN 08 Indralaya. The type of research used in conducting this research is a type of field research, which is a research process that produces qualitative descriptive data. Data collection techniques with observation, interviews, and documentation. While data analysis techniques through data reduction, data presentation, conclusion drawing. As well as data validity techniques by triangulating sources, techniques and time. The results of the study, namely, the Principal's Supervision Strategy in Improving the Performance of Islamic Education Teachers at SDN 08 Indralaya is good and in accordance with academic supervision techniques starting from planning the preparation of academic supervision programs and preparing schedules for the implementation of academic supervision. The preparation of this program was carried out at the beginning of the year and assisted by several senior teachers. Furthermore, the implementation of academic supervision using individual supervision techniques through class visits, class observations and group supervision techniques such as meetings and group discussions to supervise teacher performance at SDN 08 Indralaya and the last stage is the evaluation of academic supervision.